Creolité, migrance et gender : l’oeuvre de Gisèle Pineau - Ueckmann, Natascha (2018)
In this paper, the author proposes a theoretical and thematic of the novelistic work by Gisèle Pineau; writing marked by the issues of creolization and migrance.